KENAKALAN REMAJA DI DESA MUARA DILAM KECAMATAN KUNTO DARUSSALAM KABUPATEN ROKAN HULU - Sri Wahyu Juli; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Teenagers are the future generation who have an important role in the future in which they are also expected to perform and able to face the challenges that exist in the present and the future. The purpose of this study aims to determine the type of juvenile delinquency estuary village dilam Kunto Darus Salam subdistrict Rokan Hulu and to determine the factors causing juvenile delinquency in the village of Muara Dilam Kunto Darus Salam subdistrict Rokan Hulu. The theory used is the theory of aberration. Deviations are all actions that are not in accordance with the norms in force. Juvenile delinquency is the behavior or actions of children who violate the norms of good social norms, legal and security groups and disturb other people (society) so that security measures need to be taken by the other party.Keywords: Adolescents, Irregularities, Juvenile Delinquency